What everyone in Britain should know about crime and punishment - Wilson, David (Blackstone Press, 1998)
This book stems from frustration: a frustration born of successive governments' insistence that 'prison works'; a frustration born of the knowledge of the realities of crime and punishment, and lastly, the kind of society we are becoming when we continue to police and incarcerate at the rate we do. Since the publication of the first edition a real debate has begun about the 'war on drugs', and whilst we have continued to imprison at a rate higher than our European neighbours this book remains one of the few voices raised in opposition. Written with the support and direction of an editorial committee of prison governors, criminologists, probation officers, ex-offenders and a prominent politician, this thought-provoking book gives you the inside story on crime and punishment in Britain. This second edition has been brought entirely up-to-date with a new chapter on the courts and a discussion on the needs of victims. What Everyone in Britain Should Know About Crime and Punishment exposes our criminal justice system as a failure, lacking in justice and doing very little to tackle the causes of crime and catch offenders. Wilson and Ashton claim that despite the political rhetoric, the solutions to crime rarely lie with the police, courts, probation and prison services. Instead, they argue the solution is to be found through a greater emphasis on education, enhanced work opportunities and crime prevention, rather than the current obsession with how to punish an offender. What Everyone in Britain Should Know About Crime and Punishment has been quoted extensively by journalists and political commentators and more importantly has engaged those members of the public who have a genuine interest in knowing the truth